Scene coordinate encoding for 3D representation and relocalization - Jiang, Zeyu (Nanyang Technological University, 2025)
Visual localization, estimating the camera’s position and orientation within a known scene, is crucial for robotics, autonomous driving, and AR/VR applications. Scene Coordinate Regression (SCR) is a structure-based visual localization method that implicitly encodes the map information within the weights of a deep neural network and directly regresses the 2D-3D matches. However, in the current study, the limited learning capacity of deep neural networks renders SCR methods inadequate for representing repetitive textures and meaningless areas due to the reliance on implicit triangulation in 3D representation.